A Systematic Review of Randomized Controlled Trials on Oral Chinese Herbal Medicine for Prostate Cancer. - Huijuan Cao; Yujie Mu; Xun Li; Yuyi Wang; Shiuan Chen; Jian-Ping Liu (PLoS ONE, 2016)
Background Prostate cancer is the most common malignant tumor associated with male reproductive system. Objective The existing eligible randomized controlled trials (RCTs) were critically appraised for the safety and effectiveness of CHM for prostate cancer. Methods A literature search was conducted by using PubMed, CENTRAL, CNKI, CBM, VIP and Wanfang databases until August 2015. RCTs of CHM or CHM plus conventional medicine for prostate cancer patients were included. The primary outcomes appraised were survival time, time to progression and quality of life. The risk of bias assessment according to the Cochrane Handbook was used to evaluate the methodological quality of the included trials. Revman 5.3 software was used for data analyses. Risk ratio and mean difference (MD) with a 95% confidence interval (CI) were used as effect measures. Meta-analysis was to be used if sufficient trials without obvious clinical or statistical heterogeneity were available. Results A total of 17 RCTs involving 1224 participants were analyzed. One trial was about CHM comparing to no treatment. The remaining 16 trials used CHMs as adjunctive treatment for endocrine therapy. Due to the poor quality of methodologies of most trials, only limited evidence showed that a combination of CHM and endocrine therapy might be more effective in restraining the development of the disease (MD 10.37 months, 95%CI 9.10 to 11.63 months), increasing patients' survival time (7-15 months) or improving patients' performance status, when compared to endocrine therapy alone (Karnofsky performance scale average changed 15 scores between groups). No severe adverse event was reported related to CHM. Conclusion Due to the insufficient quality of trials that were analyzed, it is not appropriate to recommend any kind of CHMs in treating prostate cancer at the present time. Well-designed trials with high methodological quality are needed to validate the effect of CHMs for patients with prostate cancer.